Spontaneous rupture of the extensor pollicis longus tendon in a lacrosse player. Issue 6 (2nd November 2022) - Aruma, Jane-Frances; Herickhoff, Paul; Taylor, Kenneth; Seidenberg, Peter
ABSTRACT: Spontaneous rupture of the extensor pollicis longus (EPL) tendon at the wrist has been reported with predisposing factors to include distal radius fractures, rheumatoid arthritis, systemic or local steroids, and repetitive abnormal motion of the wrist joint. We present a case of an 18-year-old college lacrosse player without history of known predisposing factors who presented with an acute inability to extend the interphalangeal (IP) joint of his right thumb. Preoperative musculoskeletal ultrasound demonstrated rupture of the EPL tendon proximal to the carpometacarpal (CMC) joint of the thumb. A tendon transfer was therefore performed, where the extensor indicis proprius (EIP) was surgically rerouted to reconstruct the ruptured EPL. The athlete eventually returned to competition without sequela. We suggest that the tendon rupture was secondary to repetitive stick checking during play, causing microtrauma to his exposed dorsal wrist. Lacrosse team physicians, athletic trainers, and equipment managers should be aware of this injury mechanism and ensure that their players, and attackmen in particular, are equipped with gloves which adequately pad the dorsal wrist to decrease the risk of microtrauma to the EPL tendon.